A 3-D DENSITY-VELOCITY MODEL BETWEEN THE CRETAN SEA AND LIBYA - Makris J.; Yegorova T. (My University, 2006)
A 3-D density model for the Cretan and Libyan Seas and Crete was developed by gravity modelling constrained by five 2-D seismic lines. Velocity values of these cross-sections were used to obtain the initial densities using the Nafe-Drake and Birch empirical functions for the sediments, the crust and the upper mantle. The crust outside the Cretan Arc is 18 to 24 km thick, including 10 to 14 km thick sediments. The crust below central Crete at its thickest section, has values between 32 and 34 km, consisting of continental crust of the Aegean microplate, which is thickened by the subducted oceanic plate below the Cretan Arc. The oceanic lithosphere is decoupled from the continental along a NW-SE striking front between eastern Crete and the Island of Kythera south of Peloponnese. It plunges steeply below the southern Aegean Sea and is probably associated with the present volcanic activity of the southern Aegean Sea in agreement with published seismological observations of intermediate seismicity. Low density and velocity upper mantle below the Cretan Sea with ρ ≅ 3.25 × 103 kg/m3 and Vp velocity of compressional waves around 7.7 km/s, which are also in agreement with observed high heat flow density values, point out at the mobilization of the upper mantle material here. Outside the Hellenic Arc the upper mantle density and velocity are ρ ≥ 3.32 × 103 kg/m3 and Vp = 8.0 km/s, respectively. The crust below the Cretan Sea is thin continental of 15 to 20 km thickness, including 3 to 4 km of sediments. Thick accumulations of sediments, located to the SSW and SSE of Crete, are separated by a block of continental crust extended for more than 100 km south of Central Crete. These deep sedimentary basins are located on the oceanic crust backstopped by the continental crust of the Aegean microplate. The stretched continental margin of Africa, north of Cyrenaica, and the abruptly terminated continental Aegean microplate south of Crete are separated by oceanic lithosphere of only 60 to 80 km width at their closest proximity. To the east and west, the areas are floored by oceanic lithosphere, which rapidly widens towards the Herodotus Abyssal plain and the deep Ionian Basin of the central Mediterranean Sea. Crustal shortening between the continental margins of the Aegean microplate and Cyrenaica of North Africa influence the deformation of the sediments of the Mediterranean Ridge that has been divided in an internal and external zone. The continental margin of Cyrenaica extends for more than 80 km to the north of the African coast in form of a huge ramp, while that of the Aegean microplate is abruptly truncated by very steep fractures towards the Mediterranean Ridge. Changes in the deformation style of the sediments express differences of the tectonic processes that control them. That is, subduction to the northeast and crustal subsidence to the south of Crete. Strike-slip movement between Crete and Libya is required by seismological observations. © 2005 Elsevier B.V. All rights reserved.
Keywords: 3-D DENSITY AND VELOCITY MODEL; ACCRETION WEDGE; BOUGUER AND FREE-AIR GRAVITY; CRUSTAL STRUCTURE; EAST MEDITERRANEAN RIDGE; OBDUCTION; SUBDUCTION